The Influence of Using YouTube Media on Accuracy in Pronunciation of the Hijaiyyah Mahasiswa Letters Biology - Anggia Putri (Islamic Journal of Teaching and Learning, 2026)
Backround: Biology students face substantial challenges in accurately pronouncing Arabic hijaiyyah letters due to minimal phonological exposure and absence of equivalent sounds in Indonesian.Objective: This study evaluated the comparative effectiveness of audiovisual media versus conventional instruction in enhancing hijaiyyah pronunciation accuracy among Biology students.Method: This study employed a quantitative approach using a quasi-experimental design with a pretest-posttest control group configuration.Thirty third-semester Biology students at UIN Sunan Gunung Djati Bandung participated in a quasi-experimental study with pretest-posttest control group design. Participants were randomly assigned to experimental (audiovisual media, n=15) and control (conventional instruction, n=15) groups. The experimental intervention featured animated articulatory demonstrations and native speaker models. Assessment comprised oral tests of 28 hijaiyyah letters, structured observations, and documentation, analyzed using paired and independent t-tests. The experimental group's pronunciation accuracy increased from 52.67% to 78.33% (48.71% gain), substantially exceeding the control group's improvement from 50.87% to 58.40% (14.80% gain). Independent sample t-test confirmed significant differences (t=9.086, p<0.001).Findings and Implications: Experimental participants demonstrated superior performance across all pronunciation dimensions, particularly makharijul huruf accuracy (1.20-point advantage). Audiovisual media represents a significantly more effective pedagogical approach than traditional methods for developing Arabic pronunciation competence among science students.Conclusion: These findings support systematic integration of multimedia instruction in Arabic language curricula designed for non-linguistic majors, potentially transforming pronunciation pedagogy across diverse disciplinary contexts.